Factors Affecting Company Value in Sharia Commercial Banks in Indonesia - Sufyati HS (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of investment decisions proxied by Capital Expenditure to Book Value Assets (CEP/BVA), funding decisions proxied by Debt-to-Equity Ratio (DER), and profitability as proxied by Return on Equity (ROE) to value companies that are proxied by Earnings Per Share (EPS) at Islamic commercial banks for the 2015-2020 period. In this study, the data used are secondary data by analyzing 5 (five) samples of financial statements of Islamic commercial banks using purposive sampling method in sampling. The results of this study, it was found that Capital Expenditure to Book Value Assets (CEP/BVA) had a negative and insignificant effect on Earnings Per Share (EPS). While the Debt-to-Equity Ratio (DER) has a positive and significant effect on Earnings Per Share (EPS).